Do Japanese stock prices reflect macro fundamentals? - Wenjuan Chen; Anton Velinov (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
This paper investigates to what extent the fundamentals of the real economy are reflected in the stock prices of Japan. A Markov switching VAR model with switching variances is used to test the structural identification scheme. Identification of fundamental and nonfundamental shocks is shown to be supported by the data. Based on the appropriate structural restriction, the historical stock prices are decomposed into fundamental components and nonfundamental components. The decomposition shows that the linkage between Japanese stock prices and real activity shocks became strengthened since the bubble collapsed in the beginning of 1990s.
Keywords: G12; E23; 330; Stock price; real activity; financial crisis; structural restrictions; Börsenkurs; Aktienmarkt; Konjunktur; Finanzkrise; Makroökonomischer Einfluss; Japan